The Notation Standards in Business Communication and Accounting – Perspective of Reporting in Polish Companies - Marta MAZUROWSKA; Marta SZCZEPAŃSKA (Communications of International Proceedings, 2020)
The IBCS® notation standards are relatively new but more and more popular tool used worldwide in business reporting practice. The efficacy of the IBCS® standards have not been yet scientifically analysed and quantified on a group of managers. The purpose of the planned research is to fill this gap by indicating real behavioral impact on decision-makers who are using conventional reports and those prepared with the IBCS®. The paper starts with a brief introduction to idea of notation standards. Then, the notation standards in business communication in the context of the IBCS® are discussed. The next part of the paper presents the idea of planned research in the light of decision-making theory. The last part is devoted to a brief summary.
Keywords: Notation Standards; IBCS®; Business Communication; Accounting.